(untitled) (Indian Journal of Animal Production and Management, 2013)
Secondary data on egg production from local and improved birds in the state of Assam for the period from 1995 to 2008 were collected from State Directorate of Animal Husbandry and Veterinary Assam, Guwahati. Models viz. linear, quadratic, cubic and exponential were fitted to the yearly data for the period under reference. The cubic model revealed positive growth of local egg production with high co-efficient of determination (R2 = 0.96) followed by Quadratic model (R2 = 0.956), exponential model (R2 = 0.956) and linear model (R2 = 0.952). In case of improved egg production also, cubic model could explain highest percentage of variation (R2 = 0.896) amongst all the models with negative growth rate. Further, for overall egg production also cubic model was found to be best fit with high co-efficient of determination (R2 = 0.815) in the state during the study period. The negative correlation co-efficient of the production series (0.85) indicated the need of restructure production policy in favour of arresting negative growth of improved eggs, increase production and sustain the growth rates.